2018
DOI: 10.37706/ijaz.v3i2.74
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Governance and Efficiency on Zakat Distribution: Evidence From Indonesia

Abstract: This study analysesand identifies the governance factor(s) that influence zakat disbursement efficiency for Indonesia’s National Zakat Board (BAZNAS)in four district of Central Java Province, namely Banyumas, Purbalingga, Banjarnegara, and Kebumen. This research examines how the zakat institution in Indonesia has improved in terms of disbursement activities over the past 5 years (2011-2015).This is a quantitative research study that uses two approaches of efficiency analysis, namely (i) zakat disbursement effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…For the keyword distribution, an example of his research is Mubtadi & Susilowati (2018) analyzing the governance and efficiency of zakat distribution in Indonesia. The results of this study indicate that there is a negative effect between board size and cost efficiency and no effect with disbursement and time efficiency.…”
Section: Summary Of Bibliometric Analysis Results Of Zakat Governancementioning
confidence: 99%
“…For the keyword distribution, an example of his research is Mubtadi & Susilowati (2018) analyzing the governance and efficiency of zakat distribution in Indonesia. The results of this study indicate that there is a negative effect between board size and cost efficiency and no effect with disbursement and time efficiency.…”
Section: Summary Of Bibliometric Analysis Results Of Zakat Governancementioning
confidence: 99%
“…(Al-Ayubi et al, 2018) explained that Indonesia Zakat Institutions have many challenges with socialization expenses, volunteer numbers, zakat collection, and type of zakat distribution, which lowers their intermediation function. (Arkham Mubtadi & Susilowati, 2018) found that board size and cost efficiency negatively affect zakat distribution in Indonesia, while disbursement and time efficiency do not. Based on the explanation above, several factors can affect the efficiency of zakat distribution, including technical issues, evaluation programs, interaction design, the cost of socializing zakat, the number of volunteers, and the selection of zakat distribution type.…”
Section: Cluster 4: Zakat Efficiencymentioning
confidence: 98%
“…Behind the implementation of the zakat distribution process, human resources involved in zakat fund management have a crucial role in its efficiency. In the study by Mubtadi and Susilowati (2018), it is explained that besides professionalism among zakat institution managers, their roles in the zakat institution have a positive influence on distribution efficiency [31]. These parties need to hold strategic meetings and discussions, as mentioned by Kholis et al (2013) in the study by Mubtadi and Susilowati (2018), that increasing the number of board meetings can reduce cases of zakat fund misuse [31].…”
Section: Osmera Et Al (mentioning
confidence: 98%